An Introduction to Murine Models of Atrial Fibrillation - Riley, Genna; Syeda, Fahima; Kirchhof, Paulus; Fabritz, Larissa (Frontiers in Physiology, 2012)
Understanding the mechanism of re-entrant arrhythmias in the past 30 years has allowed the development of almost curative therapies for many rhythm disturbances. The complex, polymorphic arrhythmias of atrial fibrillation and sudden death are, unfortunately, not yet well understood, and hence still in need of adequate therapy. Atrial fibrillation contributes markedly to morbidity and mortality in ageing Western populations. In the past decade, many genetically altered murine models have been described and characterised. Here, we review genetically altered murine models of atrial fibrillation; powerful tools that will enable a better understanding of the mechanisms of atrial fibrillation and the assessment of novel therapeutic interventions.